Female Sexuality in the Early Medieval Islamic World: Gender and Sex in Arabic Literature by Pernilla Myrne (American Journal of Islam and Society, 2020)
In a fascinating passage in his epistle to Abū ʿAlī b. al-Ḥārith on differences in character, the polymath Qusṭā b. Lūqā (d. 300/912) observes that there are three kinds of sexual preference among people (al-nās): “those who incline to women, those who opt for boys (al-ghilmān) exclusively, and those who are disposed to both.”1 As the context clearly indicates, the referent of “people” here is, unsurprisingly, adult males: the minority group with whose pens and for whose edification and/or entertainment the overwhelming majority of premodern Arabic texts were composed. This is no less true in the domain of the erotic, as demonstrated by Pernilla Myrne in her outstanding recent monograph on female sexuality in the third and fourth centuries AH, which partly redresses this systematic neglect with its welcome focus on women and their agency. To read the full book review, download the PDF file on the right.